Transient Postoperative Hemorrhage from Elbow Arthroscopy Portals following Intra-Articular Pentosan Polysulfate Sodium Injection - Lindsay A. Parker; Brandan Wustefeld-Janssens; James M. Dundas (Case Reports in Veterinary Medicine)
Four adult, client owned dogs with diagnosed bilateral elbow dysplasia undergoing elbow arthroscopy for removal of fragmented medial coronoid process were identified via a retrospective database search, who also received intra-articular administration of pentosan polysulfate sodium (PPS) (Cartrophen Vet, Biopharm Australia Pty Ltd., Bondi Junction, New South Wales). Dogs had postoperative administration of 5 ml PPS injected into each elbow joint following elbow arthroscopy. Within 1-3 hours of administration, each dog experienced hemorrhage from arthroscopy incisions that was determined to be independent of surgical trauma given lack of hemorrhage intraoperatively. Pressure bandages were placed, and the hemorrhage and elevated coagulation parameters resolved 12-18 hours following intra-articular injection. No further intervention was required, and the dogs were discharged 20-26 hours postoperatively. The purpose of this case series is to describe 4 dogs who experienced transient and focal hemorrhage following off-label intra-articular administration of pentosan polysulfate sodium (PPS). While this case series is limited due to small number of cases, results following bilateral, intra-articular injection of PPS support a transient systemic coagulopathy. Though this report represents administration of PSS via a route and at doses beyond that recommended on the label, results suggest that administration of PSS in the manner described in this report should be avoided.